Digitalization of Mobile-Based Construction Material Inventory Management Using the Waterfall Model at PT Wanro Sukses Persada - Aulia, Raihan Naufal; Hidroes Abbrori, Nanang Hoesen (Journal of Digital Business and Innovation Management, 2026)
PT Wanro Sukses Persada faces constraints in construction logistics management due to a manual material recording system, which triggers various problems such as stock data inaccuracies, delayed information updates, and discrepancies between administrative records and physical conditions in the field. Therefore, this study aims to design and develop a mobile-based material stock management and monitoring application to provide real-time data and digitize the workflow. This research employs a qualitative case study method with a Software Development Life Cycle (SDLC) Waterfall model approach without the maintenance phase, where the infrastructure is built using Android Studio integrated with Firebase Realtime Database. To validate the functionality of the developed system, this study applies Black-Box Testing, focusing on testing the alignment between the software's input and output. This research produced a mobile application named "Wanro Stock App" that facilitates operational activities among management, warehouse teams, and field supervisors through features such as stock availability notifications and material request and return mechanisms. Based on the functional testing results, the developed application is capable of executing operational scenarios in accordance with the initial design, such as processing synchronous stock updates during transactions, rejecting illogical data inputs, and executing automated approval workflows. This functional alignment confirms that the Wanro Stock App has met the software's functional feasibility for implementation, making it a potential digital solution to replace the manual logistics recording method within the company.